Analysis of the Component Values of the Historic Urban Complex – the Basis for Conservation Programs and Plans - Szmygin, Boguslaw (Protection of Cultural Heritage, 2021)
The most complex problem in historic preservation is the protection of historic cities. The main problem is the need to combine the conservation requirements (restrictions on transformations) with the growing needs of modernization. The historic city needs to modernize, so conservationist must define the object, form and limits of transformation. It is therefore necessary to develop a methodology that will make it possible to link the historic values of the ensemble with their material representation. This will make it possible to identify the elements to be protected and the elements that can be transformed. The methodology of determining the material representation of historic values has been shown on the example of the historic center of Krakow inscribed on the UNESCO World Heritage List. The SMART VALUE methodology was used in the development of the Krakow Management Plan. The methodology can be used as a tool to help in the management of different groups of monuments, especially those of significant value (especially those declared as Monuments of History or World Heritage properties).